Association of Autologous Costal Cartilage Harvesting Techniques with Donor Site Pain in Patients Undergoing Augmentation Rhinoplast - Mehmood, Mehwish; Aslam, Ayesha; Aman, Sameena; Ali, Ahmed; Feroze, Hira; Saleem, Nousheen; Mumtaz, Hassan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the relationship between postoperative pain and the harvesting of autologous costal cartilage grafts using either a muscle-sparing technique with blunt dissection or a muscle-cutting technique with electrocautery in patients undergoing augmentation rhinoplasty.Study Design: Quasi-experimental study.Place and Duration of Study: Plastic Surgery Department, Fauji Foundation Hospital, Rawalpindi Pakistan, from Oct 2022 to Jun 2023.Methodology: A total of 32 patients, aged 15 to 35 years and of both genders, undergoing elective augmentation rhinoplasty with no medical comorbidities, were divided into two groups. Patients who were undergoing surgery due to acute nasal trauma, nasal patency, nasal polyps, and other pathological causes were excluded. Group-A received augmentation rhinoplasty via the muscle-sparing technique, while Group-B received the surgery via muscle-cutting technique using electrocautery. Patients in both groups were assessed in terms of postoperative donor site pain.Results: The mean age in Group-A was 20.7±5.5 years while in Group-B, it was 21.7±4.9 years. The comparison of mean pain scores at rest (p